HUBUNGAN KADAR ANTIBODI RESEPTOR ASETILKOLIN DENGAN DERAJAT KEPARAHAN PENYAKIT MIASTENIA GRAVIS DI RS CIPTO MANGUNKUSUMO - Manfaluthy Hakim,* Fika Tiara,* Ahmad Yanuar,* Winnugroho Wiratman,* Luh Ari Indriawati,* Astri Budi (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION ACETYLCHOLINE RECEPTOR ACHR ANTIBODY IS MAIN ANTIBODY IN PATHOGENESIS OF MYASTHENIA GRAVIS MG ACHR ANTIBODY IS AN IMPORTANT DIAGNOSTIC TESTS MYASTHENIA GRAVIS CLINICAL FEATURES CAN BE DIVIDED INTO OCULAR GENERALIZED AND BULBAR MG SEVERITY OF MG CAN BE ASSESSED BASED ON MG COMPOSITE SCORE MGCS